Essential Characteristics of a Primary School Teacher as a Subject of Creative Pedagogical Activity - Zhurat, Yulya; Doroshenko, Tatiana; Shaposhnikova, Iryna; Tamara, Paguta; Bader, Svetlana; Sushchenko, Tatyana (My University, 2021)
The article describes and analyzes three key aspects of the personality of a primary school teacher as a subject of creative pedagogical activity - Requirements for the personality of a modern primary school teacher, subjectivity of a primary school teacher in scientific discourse and activity components as a basis of professional subjectivity of a primary school teacher. The purpose of the article is to summarize the experience of Western and Eastern European scholars on the modern view of the components and activities of the subjectivity of the teacher of this profession in order to increase its didactic and educational effectiveness. It’s proved that the subjectivity of the primary school teacher is defined as a complex functional autonomy of the system, which is formed, developed, built and transformed by him in the process of life, acquisition of pedagogical education and experience of pedagogical activity. Such subject-oriented manifestations of the teacher's personality as activity (ability to conscious self-determination of creative pedagogical activity) are described; productivity (its complex ability, on the one hand, to transform the educational reality in the classroom into a humane educational environment and the student in the subject of creative learning, and on the other - to constant subjective, professional and professional self-development and self-improvement in teaching, improving the results of their activities and themselves as a subject of pedagogical activity.
Keywords: activity, productivity, awareness and perception, integrity, integrity and systematization, subjective properties